Studies in Greek philosophy. - Vlastos, Gregory (Princeton University Press, 1996)
Gregory Vlastos (1907-1991) was one of the twentieth century's most influential scholars of ancient philosophy. Over a span of more than fifty years, he published essays and book reviews that established his place as a leading authority on early Greek philosophy. The two volumes that comprise Studies in Greek Philosophy include nearly forty contributions by this acknowledged master of the philosophical essay. Many of these pieces are now considered to be classics in the field. Perhaps more than any other modern scholar, Gregory Vlastos was responsible for raising standards of research, analysis, and exposition in classical philosophy to new levels of excellence. His essays have served as paradigms of scholarship for several generations. Available for the first time in a comprehensive collection, these contributions reveal the author's ability to combine the skills of a philosopher, philologist, and historian of ideas in addressing some of the most difficult problems of ancient philosophy. Volume I collects Vlastos's essays on Presocratic philosophy. Wide-ranging concept studies link Greek science, religion, and politics with philosophy. Individual studies illuminate the thought of major philosophers such as Heraclitus, Parmenides, Anaxagoras, and Democritus. A magisterial series of studies on Zeno of Elea reveals the author's power in source criticism and logical analysis. Volume II contains essays on the thought of Socrates, Plato, and later thinkers and essays dealing with ethical, social, and political issues as well as metaphysics, science, and the foundations of mathematics.